2002
DOI: 10.1097/00007890-200207150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Modified right liver graft from a living donor to prevent congestion1

Abstract: Our early experience indicated the necessity of MHV drainage reconstruction in right lobe grafts, which do not have MHV trunk in certain instances. However, preoperatively, it is difficult to predict the degree of AS congestion of the right liver graft without MHV drainage reconstruction. We suggest aggressive reconstruction of MHV drainage tributaries of the AS, under the circumstances that sizable MHV tributaries are encountered, to prevent possible congestion-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(56 citation statements)
references
References 17 publications
0
54
0
2
Order By: Relevance
“…It has been demonstrated that ligation of large MHV tributaries could bring about more remarkable perfusion imbalance between anterior and posterior segments [42]. As a result, the vascular diameter of the MHV tributaries is the mostly recommended criteria for reconstruction and 5 mm is commonly preferred as a demarcation [13,14,16,17,18,19,20,21,23,25,26,28,29,30,32,35], while others have suggested that MHV reconstruction should be based on the clamping test findings [13,17,21,26,29,32,35], graft volume [21,23,43] and the number of the MHV tributaries [23,24,31,33]. The policy of our center for MHV tributaries reconstruction had been described above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that ligation of large MHV tributaries could bring about more remarkable perfusion imbalance between anterior and posterior segments [42]. As a result, the vascular diameter of the MHV tributaries is the mostly recommended criteria for reconstruction and 5 mm is commonly preferred as a demarcation [13,14,16,17,18,19,20,21,23,25,26,28,29,30,32,35], while others have suggested that MHV reconstruction should be based on the clamping test findings [13,17,21,26,29,32,35], graft volume [21,23,43] and the number of the MHV tributaries [23,24,31,33]. The policy of our center for MHV tributaries reconstruction had been described above.…”
Section: Discussionmentioning
confidence: 99%
“…Cryoperserved cadaveric iliac vein and artery have been proved to effectively solve drainage problems of the paramedian portion of the right lobe [10,18,19]. The initial vessel material for MHV reconstruction was recipient GSV [13], which was preferred for interposition during the early period at our center, and then it was taken over by CIAs because we found that it was easier to obtain a large-sized outflow orifice when CIAs were used for reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified right lobe graft [7] was used in 10 patients. Extended right lobe graft [8] and right lobe graft without middle hepatic vein reconstruction were used in 4 and 2 cases respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, the late obstructions of these ePTFE graft were all asymptomatic and had no impact on postoperative liver congestion, liver regeneration, or patient survival. With respect to the duration of graft patency, one to two weeks is considered to be enough to maintain adequate liver graft function because intrahepatic venous collateral can be expected to develop within one week of the operation [20]. Another report has described the conversion of the portal tract to an outflow channel within one hour, and intrahepatic venous collateral formation within two weeks when the hepatic vein was occluded [21].…”
Section: Discussionmentioning
confidence: 99%